A Severe Lack of Evidence Limits Effective Conservation of the World's Primates. (26th August 2020) - Junker, Jessica; Petrovan, Silviu O; Arroyo-RodrÍguez, Victor; Boonratana, Ramesh; Byler, Dirck; Chapman, Colin A; Chetry, Dilip; Cheyne, Susan M; Cornejo, Fanny M; CortÉs-Ortiz, Liliana; Cowlishaw, Guy; Christie, Alec P; et al.
Abstract: Threats to biodiversity are well documented. However, to effectively conserve species and their habitats, we need to know which conservation interventions do (or do not) work. Evidence-based conservation evaluates interventions within a scientific framework. The Conservation Evidence project has summarized thousands of studies testing conservation interventions and compiled these as synopses for various habitats and taxa. In the present article, we analyzed the interventions assessed in the primate synopsis and compared these with other taxa. We found that despite intensive efforts to study primates and the extensive threats they face, less than 1% of primate studies evaluated conservation effectiveness. The studies often lacked quantitative data, failed to undertake postimplementation monitoring of populations or individuals, or implemented several interventions at once. Furthermore, the studies were biased toward specific taxa, geographic regions, and interventions. We describe barriers for testing primate conservation interventions and propose actions to improve the conservation evidence base to protect this endangered and globally important taxon.